Lûds′ka gidnist′ u pravì : fìlosofs′ko – pravovij vimìr - Griŝuk, Oksana (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
This article is a comprehensive research of Human Dignity in Law based upon modern legal scientific literature, international and national legal acts. Human nature is treated as a unity of biological, social and spiritual elements of existence of the human person. The Natural Law is based on spiritual existence of the human person because it opens value of the human being – human dignity. At the contemporary stage of development of Ukraine real social and legal progress is impossible without due defense human dignity. Therefore human dignity is a source of the Law and human rights.
Keywords: godność człowieka; prawo; wymiar filozoficzno-prawny